Perlindungan Konsumen Terkait Harga Yang Berbeda di Rak Barang Dengan Struk di Kasir - Taun Taun; Naili Sa’adah (Peneliti.net, 2022)
Discussing consumer protection is very interesting, because it is related to daily life, one can become a consumer and one can become a business actor. Many consumers and business actors do not understand their rights, obligations and responsibilities. There are important legal rules as the basis for consumer protection policies in Indonesia. First, the 1945 Constitution, as a source of law in Indonesia, mandates that national development aims to create a just and prosperous society. To realize a democratic economic development system so that it can grow and develop a world that produces goods and services that are suitable for consumption by the community. Second, Law Number 8 of 1999 concerning Consumer Protection. The enactment of this Law provides hope for the Indonesian people, to obtain protection from losses suffered on transactions of goods and services, where the Consumer Protection Act guarantees legal certainty for consumers.